Selection and validation of optimal reference genes for RT-qPCR analyses in Aphidoletes aphidimyza Rondani (Diptera: Cecidomyiidae) - Shen, Xiu-Xian; Zhang, Guo-Qiang; Zhao, Yu-Xin; Zhu, Xiao-Xiao; Yu, Xiao-Fei; Yang, Mao-Fa; Zhang, Feng (Frontiers in Physiology, 2023)
Aphidoletes aphidimyza is a predator that is an important biological agent used to control agricultural and forestry aphids. Although many studies have investigated its biological and ecological characteristics, few molecular studies have been reported. The current study was performed to identify suitable reference genes to facilitate future gene expression and function analyses via quantitative reverse transcription PCR. Eight reference genes glyceraldehyde-3-phosphate dehydrogenase (GAPDH), RPS13, RPL8, RPS3, α Tub, 𝛽-actin, RPL32, and elongation factor 1 alpha (EF1-α) were selected. Their expression levels were determined under four different experimental conditions (developmental stages, adult tissues, sugar treatment, and starvation treatment) using qRT-PCR technology. The stability was evaluated with five methods (Ct value, geNorm, NormFinder, BestKeeper, and RefFinder). The results showed that GAPDH, RPL32, and EF1-α were ranked as the best reference gene combinations for measuring gene expression levels among different developing stages and in various starvation treatments. RPL8 and RPS3 were recommended to normalize the gene expression levels among different adult tissues. RPL32, 𝛽-actin, and EF1-α were recommended sugar-feeding conditions. To validate the utility of the selected reference pair, RPL8, and RPS3, we estimated the tissue-biased expression level of a chemosensory protein gene (AaphCSP1). As expected, AaphCSP1 is highly expressed in the antennae and lowly expressed in the abdomen. These findings will lay the foundation for future research on the molecular physiology and biochemistry of A. aphidimyza.